1989
DOI: 10.1172/jci114233
|View full text |Cite
|
Sign up to set email alerts
|

Human platelets modulate edema formation in isolated rabbit lungs.

Abstract: The role of platelet glucose-6-phosphate dehydrogenase (G-6-PD) in mediating the effects of human platelets on oxidant-induced edema in the isolated perfused rabbit lung was investigated using dehydroepiandrosterone, a specific steroidal inhibitor of G-6-PD. Xanthine oxidase (0.003 and 0.012 U/ml) caused lung edema that was attenuated by coinfusion of washed human platelets. Platelets that were incubated with DEA to inhibit G-6-PD activity augmented xanthine oxidase-induced lung edema and pulmonary hypertensio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…However, it is possible that in the presence of PAF-induced cell disjunction, vasoconstrictors may raise hydrostatic pressure by postcapillary vasoconstriction and consequently, potentiate plasma leakage. Our data, as well as those presented by Heffner et al (1989), strongly support this hypothesis. It appears that vascular permeability is only modulated by changes in blood pressure.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is possible that in the presence of PAF-induced cell disjunction, vasoconstrictors may raise hydrostatic pressure by postcapillary vasoconstriction and consequently, potentiate plasma leakage. Our data, as well as those presented by Heffner et al (1989), strongly support this hypothesis. It appears that vascular permeability is only modulated by changes in blood pressure.…”
Section: Discussionsupporting
confidence: 91%
“…These results indicate that considerably severe ALI was induced during the 90-min observation period. Our oxidant-induced ALI model has been well established in many studies [9,12,13]. We also tried to carry out a histological examination.…”
Section: Discussionmentioning
confidence: 99%
“…Piso is the pulmonary capillary pressure at which the lung neither gains nor loses weight, where the Starling forces are balanced [11][12][13]. Piso was determined by discontinuing perfusion and opening a shunt between the two cannulae, so that the Ppa and Pla were equal.…”
Section: Measurement Of Piso and Kfcmentioning
confidence: 99%
See 1 more Smart Citation
“…In the sheep lung fistula model, animals rendered thrombocytopenic for 3 days with antiplatelet serum develop increased pulmonary vascular permeability to protein [13]. In endothelial cell cultures and ex vivo lung models, our own investigations have demonstrated that platelets attenuate tissue injury related to chemical oxidant systems and ischemia reperfusion [14][15][16][17]. The mechanisms for these protective effects are unknown, but may relate to the delivery of platelet antioxidants to regions of oxidant stress [16,17], the release of adenosine leading to increased endothelial cell stores of cAMP [18,19] or the provision of serotonin to cell membranes [20].…”
Section: J E Heffnermentioning
confidence: 99%